The impact of the Brexit vote on UK financial markets: A synthetic control method approach - Matej Opatrny (Charles University in Prague, Institute of Economic Studies (IES), 2019)
We estimate how the UK financial markets would have evolved if the Remain camp had won the referendum. To construct thecounterfactual, we use the synthetic control method. Our results suggest that there would not have been any significant change in the development of the FTSE 100 Index in the medium to long term if there had not been a referendum. On the other hand, we find a significantly negative effect of 1.2 percentage points on the 10-year bond yield. Given the geopolitical circumstances in mid 2016, financial agents investing in the pound could have sought safer investment options represented by longer-term government bonds, which consequently could result in lower bond yields.
Keywords: C10; Q10; Q18; 330; Brexit; financial markets; macroeconomic indicators; synthetic control method